Shark long line gear of India - Varghese, M.D.; Kuttappan, A.C., Ramarao, S.V.S., Mathai, P.G., George, V.C., Kunjipalu, K.K. (Fishery Technology, 2021)
Sharks are mainly harvested with long lines which is less expensive compared to other methods of fishing. Though this is a common gear operated along the coast, the gear in every region has its own peculiarities in construction and rigging. This communication furnishes detailed description of the gear operated in different centres. Suggestions are also offered to improve the gear and methods for enhancing production.